Antidepressant treatment trajectories and suicide attempt among Australians aged 45 years and older: A population study using individual prescription data. Issue 1 (25th October 2021) - Carter, Gregory; Sperandei, Sandro; Chitty, Kate M.; Page, Andrew
Abstract: Introduction: Meta‐analyses show antidepressant initiation has increased risk of suicidal behavior <25 years, no difference 25–64 years and reduced risk 65+ years. Estimating risks from RCTs has limitations and real‐world population estimates are uncommon. Methods: A self‐controlled case series reporting incidence rate ratio (IRR) between exposed and control periods for antidepressants associated with suicide attempt, in Australian older age adults. We included all cases with suicide attempt [hospital data for ICD codes (X60–X84)] and any antidepressant use ( n = 689) by participants in the "45 and Up Study". Results: For all antidepressants the IRR for suicide attempt was elevated across all exposures, declining from 7.44 (95%CI 5.57–9.94) during the first 30 days, to 2.21 (1.73–2.81) at 91+ days. All four antidepressant sub‐groups had higher IRRs for the first 30 day exposure: 2.43 (1.37–4.29) for TCAs, 4.06 (2.78–5.93) for SSRIs, 4.15 (2.65–6.50) for other antidepressants, and 4.92 (3.30–7.34) for SNRIs. Increased IRR persisted for 61‐ to 90‐day exposures for SSRIs 2.42 (1.18–4.98) and SNRIs 2.66 (1.34–5.27). Conclusion: Some older adults have increased risk of suicide attempt with antidepressant exposure, which may persist for months. Clinical guidelines should recommend a period of monitoring for treatment‐emergent suicidal thoughts and behaviors in older adult patients.